Nectar production in the pollen flower of Anemone nemorosa in comparison with other Ranunculaceae and Magnolia (Magnoliaceae) - Erbar, Claudia; Leins, Peter (Organisms, diversity & evolution, 2013)
The observation that the flowers of Anemone nemorosa offer nectar to pollinating bee-flies (Bombylius major) prompted this investigation into the site of nectar secretion and nectary tissue. To allow comparison on a broader basis, other nectar-secreting pollen flowers of the Ranunculaceae and Magnolia (Magnoliaceae) were included in the analysis. The contradictory information available on the function of the mouthparts of bee-flies during nectar and pollen feeding motivated us to investigate the proboscis structure in detail by SEM. Our investigations in Anemone nemorosa proved, for the first time, nectar secretion in the genus Anemone s.s. (i.e. other than the Pulsatilla group) and in addition, within the family, a new type of a carpellary nectary. The latter is an epithelial nectary involving the whole epidermis of the ovarian part of the carpel. The nectary of Anemone nemorosa resembles that of Magnolia (e.g. M. stellata), which we re-investigated. In both Anemone nemorosa and Magnolia stellata, nectar production is limited mainly to the female phase of the proterogynous flower. In this way, the attractiveness of the flower is also assured in the non-pollen presenting phase. Especially in Magnolia, with its numerous carpels arranged on a cone-like receptacle, the economic disadvantage of a choricarpous- compared to a coenocarpous-gynoecium is compensated for by nectar secretion by each carpel. When licking up the nectar droplets from the carpel surfaces, contact of the insect's body with each stigma may be achieved.
Gesehen am 12.02.2021